The associations of cholesterol metabolism and plasma plant sterols with all-cause and cardiovascular mortality[S] - Guenther Silbernagel (Journal of Lipid Research, 2010)
Moderately elevated levels of plasma plant sterols have been suspected to be causally involved in atherosclerosis. The aim of this study was to investigate whether plant sterols and other markers of sterol metabolism predicted all-cause and cardiovascular mortality in participants of the Ludwigshafen Risk and Cardiovascular health (LURIC) study. A total of 1,257 individuals who did not use statins and at baseline had a mean (± SD) age of 62.8 (± 11.0) years were included in the present analysis. Lathosterol, cholestanol, campesterol, and sitosterol were measured to estimate cholesterol synthesis and absorption. The mean (± SD) time of the follow-up for all-cause and cardiovascular mortality was 7.32 (± 2.3) years. All-cause (P = 0.001) and cardiovascular (P = 0.006) mortality were decreased in the highest versus the lowest lathosterol to cholesterol tertile. In contrast, subjects in the third cholestanol to cholesterol tertile had increased all-cause (P < 0.001) and cardiovascular mortality (P = 0.010) compared with individuals in the first tertile. The third campesterol to cholesterol tertile was associated with increased all-cause mortality (P = 0.025). Sitosterol to cholesterol tertiles were not significantly related to all-cause or cardiovascular mortality. The data suggest that high absorption and low synthesis of cholesterol predict increased all-cause and cardiovascular mortality in LURIC participants.